2015
DOI: 10.1002/asi.23367
|View full text |Cite
|
Sign up to set email alerts
|

The invariant distribution of references in scientific articles

Abstract: The organization of scientific papers typically follows a standardized pattern, the well-known IMRaD structure (introduction, methods, results, and discussion). Using the full text of 45,000 papers published in the PLoS series of journals as a case study, this paper investigates, from the viewpoint of bibliometrics, how references are distributed along the structure of scientific papers as well as the age of these cited references. Once the sections of articles are realigned to follow the IMRaD sequence, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 22 publications
6
63
1
3
Order By: Relevance
“…Second, citations are most concentrated in the Background and Summary section, with 36.5% of 949 sentences containing at least one citation, a proportion significantly higher compared to 16.3% across all sections. The latter observation is comparable to Bertin et al ()'s finding based on an examination of research papers across all Public Library of Science (PLoS) journals. This suggests that the Background and Summary section in data papers plays similar “stage setting” roles as the Introduction section in research papers (Swales, , pp.…”
Section: Preliminary Resultssupporting
confidence: 84%
“…Second, citations are most concentrated in the Background and Summary section, with 36.5% of 949 sentences containing at least one citation, a proportion significantly higher compared to 16.3% across all sections. The latter observation is comparable to Bertin et al ()'s finding based on an examination of research papers across all Public Library of Science (PLoS) journals. This suggests that the Background and Summary section in data papers plays similar “stage setting” roles as the Introduction section in research papers (Swales, , pp.…”
Section: Preliminary Resultssupporting
confidence: 84%
“…(Hu et al, ) found that references cited in the first parts of an article have globally higher citation rates. (Bertin et al, ) found invariant schemes of distribution of citation in the position of citations, but (Boyack et al, ) found important differences across disciplines. The underlying hypothesis in this study and in the current paper is that the position of a given citation is influenced by its relative importance or function.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…The IMRaD (Introduction, Methods, Results and Discussion) prototypical structure has been thoroughly described in the literature, as it is prescribed (and followed) for most science articles (Swales, ). Several recent studies of citation behaviour have focused on the section in which a citation appears, whether to study linguistic variations in the context (Bertin & Atanassova, ), the age of a citation (Bertin et al, ), or its function (Teufel, ). In order to explore this aspect, we manually tagged each section heading in our corpus according to the IMRaD categories.…”
Section: Analysis and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to do so, we processed the section titles using a set of regular expressions specifically designed for this task. After analyzing the density of citations along the four main section types, we showed that the distribution of references along the text progression is essentially invariant across the different PLOS journals []. This first result showed that a strong relation exists between the IMRaD structure and the use of citations in scientific writing.…”
Section: Creating a Map Of Citation Contextsmentioning
confidence: 99%